Implementation of FHIR SATUSEHAT API in Hospital Information System Applications - Hafiizh Asrofil, Al Banna; Wahyuningdiah Trisari, Harsanti Putri (INTI International University, 2023)
Healthcare facilities (fasyankes) provide various healthcare services to the public, such as inpatient care, outpatient care, emergency care, and others, which are largely dominated by hospitals. Healthcare activities are closely associated with patient data, which serves as a reference for patient treatment. In fasyankes term, this is commonly known as medical records; however, according to Indonesian Ministry regulations, appropriate recording is done in the form of electronic medical records. Therefore, a system is needed to handle this recording, and one of these systems is the Hospital Management Information System (SIMRS). In recording electronic medical records, various fasyankes across Indonesia differ in how they record and store these records. As a result, the Ministry of Health introduced the SATUSEHAT platform as a standard for medical record keeping. The core idea behind the SATUSEHAT platform is that healthcare facilities are primarily obligated to record medical records within the SATUSEHAT health system platform launched by the Indonesian Ministry of Health. However, a question arises: “Can this SATUSEHAT platform be implemented in hospital applications across Indonesia?” To address this question, the author makes use of the Agile Scrum method to attempt the integration of fasyankes' medical records, mainly those of hospitals, with the SATUSEHAT platform. Furthermore, the use of the SATUSEHAT platform in this research is within its development stage, subject to constant changes, making the Agile Scrum method a suitable approach. The conclusion drawn by the author from this study is that the implementation of the SATUSEHAT platform is possible, even though some features may not be fully usable.